Agenda setting for essential medicines policy in sub-Saharan Africa: a retrospective policy analysis using Kingdon's multiple streams model - Alison T. Mhazo; Charles C. Maponga (BMC, 2021)
Abstract Background Lack of access to essential medicines presents a significant threat to achieving universal health coverage (UHC) in sub-Saharan Africa. Although it is acknowledged that essential medicines policies do not rise and stay on the policy agenda solely through rational deliberation and consideration of technical merits, policy theory is rarely used to direct and guide analysis to inform future policy implementation. We used Kingdon's model to analyse agenda setting for essential medicines policy in sub-Saharan Africa during the formative phase of the primary healthcare (PHC) concept. Methods We retrospectively analysed 49 published articles and 11 policy documents. We used selected search terms in EMBASE and MEDLINE electronic databases to identify relevant published studies. Policy documents were obtained through hand searching of selected websites. We also reviewed the timeline of essential medicines policy milestones contained in the Flagship Report, Medicines in Health Systems: Advancing access, affordability and appropriate use, released by WHO in 2014. Kingdon's model was used as a lens to interpret the findings. Results We found that unsustainable rise in drug expenditure, inequitable access to drugs and irrational use of drugs were considered as problems in the mid-1970s. As a policy response, the essential drugs concept was introduced. A window of opportunity presented when provision of essential drugs was identified as one of the eight components of PHC. During implementation, policy contradictions emerged as political and policy actors framed the problems and perceived the effectiveness of policy responses in a manner that was amenable to their own interests and objectives. Conclusion We found that effective implementation of an essential medicines policy under PHC was constrained by prioritization of trade over public health in the politics stream, inadequate systems thinking in the policy stream and promotion of economic-oriented reforms in both the politics and policy streams. These lessons from the PHC era could prove useful in improving the approach to contemporary UHC policies.